Pine mires as key early-season habitat selection sites for Willow Tits in managed boreal forests - Hamedani Raja, Pegah; Baroni, Daniele; Laaksonen, Toni; Brommer, Jon Egbert (Elsevier BV, 2026)
Widespread forestry operations have simplified and fragmented boreal forest structure across Europe, reducing key features such as deadwood and peatlands that support forest specialist species. The Willow Tit (Poecile montanus), a declining boreal passerine, is highly sensitive to such changes. While its breeding-season habitat associations are relatively well studied, much less is known about its habitat use during the pre-breeding period, a critical phase of territory establishment that may influence reproductive success. We used passive acoustic monitoring (PAM) at 285 forest sites across a managed boreal landscape in southern Finland to investigate early-season Willow Tit occurrence in relation to forest structure. Species presence was modeled as a function of habitat structure (e.g., modeled deadwood potential, peatland type, foliage biomass, forest age), biotic interactions (presence of Pygmy Owl (Glaucidium passerinum) and Crested Tit (Lophophanes cristatus)), and proximity to human settlements, at two spatial scales (100 m and 400 m buffers). Willow Tit presence was consistently and positively associated with the area of pine mires, highlighting the ecological value of these pine-dominated peatlands during territory settlement. In contrast, mature forest area and modeled deadwood potential showed no positive effects; the latter exhibited a weak negative association at the landscape scale. This pattern may indicate that modeled deadwood estimates do not fully capture the fine-scale characteristics relevant for Willow Tits during the pre-breeding period, or that decaying wood plays a more limited role in habitat selection at this stage than at later stages of breeding. Detection probability declined with Julian date, likely reflecting seasonal changes in vocal activity. These findings emphasize the ecological and management importance of preserving pine mires and suggest that widely used forest inventory models may overlook key habitat features essential for declining species. We recommend integrating peatland preservation into forestry planning to enhance habitat suitability and resilience under intensive forest management and climate change.